WITHDRAWN: Treatment discontinuation with selective serotonin reuptake inhibitors (SSRIs) versus tricyclic antidepressants (TCAs). - Barbui, C; Hotopf, M; Freemantle, N; Boynton, J; Churchill, R; Eccles, M; Geddes, JR; Hardy, R; Lewis, G; Mason, J (2006)
BACKGROUND: Selective serotonin reuptake inhibitors are thought to have better discontinuation rates (i.e. less people dropping out) than tricyclic and heterocyclic antidepressant drugs. It is important to quantify the drop-out rates of different antidepressant drugs in order to have a better understanding of the relative tolerability of these drugs. OBJECTIVES: To assess the comparative tolerability of selective serotonin reuptake inhibitors and tricyclic/heterocyclic antidepressant drugs. SEARCH STRATEGY: We searched the Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Registers (1997 to 1999), MEDLINE (1966 to 1999), EMBASE (1974 to 1999) We also searched specialist journals, the reference lists of relevant papers and previous systematic reviews, conference abstracts and government documents. Representatives of the pharmaceutical industry were contacted. SELECTION CRITERIA: Parallel group randomised controlled trials comparing selective serotonin reuptake inhibitors with tricyclic or heterocyclic antidepressants in people with depression. DATA COLLECTION AND ANALYSIS: Two reviewers independently extracted data and a third reviewer checked any cases of disagreement. MAIN RESULTS: We included 136 trials. The selective serotonin reuptake inhibitors showed less participants dropping out compared to the tricyclic/heterocyclic group (odds ratio 1.21, 95% confidence interval 1.12 to 1.30). A statistically significant difference was found in total drop-outs between the selective serotonin reuptake inhibitors and the old tricyclics as well as the newer tricyclics. When the selective serotonin reuptake inhibitors were compared to the heterocyclic antidepressants, there was a non significant difference favouring the selective serotonin reuptake inhibitors. The poor tolerability profile of the old tricyclics was explained by differences in drop-outs for side-effects, but not for inefficacy. AUTHORS' CONCLUSIONS: Whilst selective serotonin reuptake inhibitors do appear to show an advantage over tricyclic drugs in terms of total drop-outs, this advantage is relatively modest. This has implications for pharmaco-economic models, some of which may have overestimated the difference of drop-out rates between selective serotonin reuptake inhibitors and tricyclic antidepressants. These results are based on short-term randomised controlled trials, and may not generalise into clinical practice.